Characterization of P69E and P69F, Two Differentially Regulated Genes Encoding New Members of the Subtilisin-Like Proteinase Family from Tomato Plants - Jordá, Lucia (American Society of Plant Physiologists, 2000)
Subtilisin-like proteins represent an ancient family of serine proteases that are extremely widespread in living organisms. We report here the structure and genomic organization of two new transcriptionally active genes encoding proteins that belong to the P69 family of subtilisin-like proteases from tomato (Lycopersicon esculentum) plants. The two new members, P69E and P69F, are organized in a cluster and arranged in a tandem form. mRNA expression analysis and studies of transgenic Arabidopsis plants transformed with promoter-β-glucuronidase fusions for each of these two genes revealed that they are differentially regulated, with each showing a highly specific mRNA expression pattern. P69E mRNA is expressed only in roots, while P69F mRNA is expressed only in hydathodes. A comparison of all the P69 amino acid sequences, gene structure, expression profiles, and clustered organization suggests a working model for P69 gene family evolution.